Coexpression of human perforin improves yeast-mediated delivery of DNA and mRNA to mammalian antigen-presenting cells - Walch-Rückheim, Barbara; Kiefer, Ruth Annabelle; Geginat, Gernot; Schmitt, Manfred J.; Breinig, Frank (Gene therapy, 2016)
Previous studies underlined the capacity of recombinant yeast as efficient vehicle for the targeted delivery of functional nucleic acids as well as proteinaceous antigens to mammalian antigen-presenting cells (APCs). To improve this yeast-mediated cargo transport into APCs, we investigated the impact of coexpression of the human membrane-perturbing protein perforin in comparison with bacterial listeriolysin O (LLO) on the yeast-based delivery of DNA, mRNA and proteins to mammalian APCs. In contrast to LLO, a cholesterol-dependent pore-forming toxin of Listeria, intracellular expression of human perforin in Saccharomyces cerevisiae had no impact on yeast cell viability, while its coexpression significantly increased translocation of ovalbumin and subsequent activation of ovalbumin-specific T lymphocytes. Likewise, perforin improved the expression of the model antigen enhanced green fluorescent protein after yeast-mediated DNA and mRNA delivery, whereas LLO was only able to enhance DNA delivery. Taken together, our data show that human perforin, besides bacterial hemolysins, represents a promising means to improve the yeast-mediated delivery of functional nucleic acids and proteins to mammalian APCs.
Published online 20 August 2015
Gesehen am 13.06.2019